2021
DOI: 10.1055/a-1422-3243
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Various Androgens on Polycystic Ovary Syndrome

Abstract: The hyperandrogenism in polycystic ovary syndrome (PCOS) is associated with the risk for the future development of the cardiovascular disease. The objective of the study is to verify whether different androgens have the same harmful effect. This cross-sectional study enrolled 823 women with PCOS: 627 (76.2%) with biochemical hyperandrogenism and 196 (23.8%) with normal androgen levels. The role of individual androgen was evaluated using univariate and multivariate logistic regression. In normoandrogenemic PCOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 89 publications
(110 reference statements)
1
10
0
Order By: Relevance
“…Our results also go in line with Cai et al [41] who observed that FAI was positively associated with WC, BMI, TG, TC and LDL-C and negatively associated with HDL-C. Recently, de Medeiros et al [42] reported a positive association of FAI with most anthropometric and metabolic biomarkers in PCOS women. Al Kindi et al [43] recommended the use of FAI than testosterone alone in the routine investigation for hyperandrogenism in women.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also go in line with Cai et al [41] who observed that FAI was positively associated with WC, BMI, TG, TC and LDL-C and negatively associated with HDL-C. Recently, de Medeiros et al [42] reported a positive association of FAI with most anthropometric and metabolic biomarkers in PCOS women. Al Kindi et al [43] recommended the use of FAI than testosterone alone in the routine investigation for hyperandrogenism in women.…”
Section: Discussionsupporting
confidence: 92%
“…In PCOS, androgens have deleterious impacts on adipose tissue function. The influence of androgens on adipocyte function is determined by levels of circulating androgen, “androgen receptor density and affinity,” [ 16 ] and the enzymatic activity of local steroids. The ability of adipocytes to modulate steroidogenic enzyme activity is of particular importance in the progression of hyperandrogenism in PCOS due to the conversion of weak androgens to strong androgens.…”
Section: Androgen Effects On Adipocytes and Steroid Production In Pcosmentioning
confidence: 99%
“…For this reason, the interrelation of hyperandrogenism and obesity in women with PCOS may originate from increased adipocyte steroidogenesis. With regards to androgen receptors, which are present on preadipocytes as well as mature adipocytes, androgens can affect gene expression, cell differentiation, and proliferation, “and carbohydrate and lipid metabolism” [ 16 ]. Androgens also increase the transcription of androgen receptors on mononuclear cells allowing for the release of adipocytokines, and the concentration of adipocytokines is further increased through production by immune cells.…”
Section: Androgen Effects On Adipocytes and Steroid Production In Pcosmentioning
confidence: 99%
See 2 more Smart Citations